Safeguarding the euro as a currency beyond the state - Ad van Riet (European Central Bank (ECB), 2016)
This paper reviews the debate on the longer-term requirements for safeguarding the euro as a currency beyond the state that is anchored through collective governance instead of a central government. The strengthening of EU economic and financial governance in the wake of the euro area crisis goes a long way towards creating the minimum conditions for a more perfect EMU. At the same time, the current principle of nation states coordinating their sovereignty to `do whatever is required' to stabilise the euro area as a whole rather than sharing their sovereignty in common institutions to achieve this common objective has its limitations. Challenges in this context relate inter alia to the effectiveness of market discipline and reinforced economic policy surveillance, the requirement of a truly single financial system, the demand for eurobonds and a euro area fiscal capacity, and the transnational democracy that should legitimate EMU decision-making based on common values. To safeguard the euro as a currency beyond the state, euro area countries should consider pooling their national sovereignty over a wider range of EMU-related policy areas, as necessary to achieve more effective risk control and more efficient risk sharing.
Keywords: E4; E6; F15; F33; 330; collective governance; euro area stability; national sovereignty